Antiallergic Effects of Callerya atropurpurea Extract In Vitro and in an In Vivo Atopic Dermatitis Model - Wooram Choi; Hwa Pyoung Lee; Philaxay Manilack; Veosavanh Saysavanh; Byoung-Hee Lee; Sarah Lee; Eunji Kim; Jae Youl Cho (Plants, 2023)
(1) Background: Callerya atropurpurea is found in Laos, Thailand, and Vietnam. Although the anti-inflammatory action of C. atropurpurea has been investigated, the functions of this plant in allergic responses are not understood. Here, we explored the antiallergic mechanism of C. atropurpurea ethanol extract (Ca-EE) using in vitro assays and an in vivo atopic model. (2) Methods: The constituents of Ca-EE were analyzed using GC/MS. Inhibition of lipoxygenase and β-hexosaminidase activity was examined, and the expression of inflammatory genes was measured by quantitative real-time PCR. The regulatory roles of Ca-EE in IgE/FcεRI signaling were examined by Western blotting. The DNCB-induced atopic dermatitis mouse model was performed with histological analysis. (3) Results: Ca-EE comprised cis-raphasatin, lupeol, some sugars, and fatty acids. In RBL-2H3 cells, treatment with Ca-EE significantly reduced the activities of lipoxygenase and β-hexosaminidase, as well as cytokine gene expression. IgE-mediated signaling was downregulated by blocking Lyn kinases. Moreover, Ca-EE effectively inhibited allergic symptoms in the DNCB-induced atopic dermatitis model without toxicity. (4) Conclusions: Ca-EE displayed antiallergic activities through regulating IgE/Lyn signaling in RBL-2H3 cells and a contact dermatitis model. These results indicate that Ca-EE could be effective for allergic disease treatment.